Du « temps des patrons » au « temps des droits » : conflits interethniques et transformations politiques chez les Ashaninka d’Amazonie brésilienne - José Pimenta (Journal de la Société des Américanistes)
The struggle of the Ashaninka of the Amonia River for land demarcation began in the 1980s at the peak of lumber extraction in their territory, and lasted until the early 1990s. For the Ashaninka this was a transition period between the « time of bosses » and the « time of rights » which they deem a key moment in their recent history. First, this article describes this « time of bosses » and shows how, with the support of various indigenist agents, the Ashaninka organized themselves to expel the invaders and the lumber companies. We then analyze this unusual historical moment, with special emphasis on the changes that occurred in the Indians’ social organization, mostly in its political sphere.